Commentary on ESMA Guidelines on enforcement of financial information - Hans-Joachim Böcking; Marius Gros; Daniel Worret (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
The document responds to 20 questions posed by the European Securities and Markets Authority (ESMA) in Annex 1 of the Consultation Paper "ESMA Guidelines on enforcement of financial information".
urn:nbn:de:hebis:30:3-322871
Keywords: 330; Enforcement; ESMA; financial reporting quality; restatements